miRNA control of tumor cell invasion and metastasis - Baranwal, Somesh (2010)
MicroRNAs have emerged as a novel class of non-coding RNAs that regulate gene expression at the post-translational level in almost every biological event. A large body of evidence indicates that microRNAs regulate the expression of different genes that play an important role in cancer cell invasion, migration, and metastasis. In this review, we briefly describe the role of various miRNAs in invasion, migration, and metastasis which are essential steps during cancer progression.